2020
DOI: 10.1371/journal.pone.0237036
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle cystatin c is associated with unstable angina in troponin negative patients with acute chest pain

Abstract: Background Despite the use of high-sensitive cardiac troponin there remains a group of high-sensitive cardiac troponin negative patients with unstable angina with a non-neglectable risk for future adverse cardiovascular events, emphasising the need for additional risk stratification. Plasma extracellular vesicles are small bilayer membrane vesicles known for their potential role as biomarker source. Their role in unstable angina remains unexplored. We investigate if extracellular vesicle proteins are associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For this, two EV subpopulations were isolated. The isolation was performed as described in previous publications 30 , 31 . In brief, a subset of EVs co-precipitate with low-density lipid particles (LDL) which allows separation.…”
Section: Methodsmentioning
confidence: 99%
“…For this, two EV subpopulations were isolated. The isolation was performed as described in previous publications 30 , 31 . In brief, a subset of EVs co-precipitate with low-density lipid particles (LDL) which allows separation.…”
Section: Methodsmentioning
confidence: 99%
“…A different study found an independent association between the extent of CVD and the levels of EV-CD14 [111]. Several other studies investigated the role of EV content in ACS, heart failure, unstable angina and manifest CVD [112][113][114].…”
Section: Extracellular Vesicle Contentmentioning
confidence: 98%
“…In CVD pathologies, alterations in circulating EV enumeration 212 and composition (miRNAs, 213,214 circular RNAs, 215 proteins [216][217][218][219] ) are also reflected in biofluids such as blood and have prognostic value in predicting cardiovascular events, 213 assessing cardiac damage, 214,215 early detections of acute coronary syndromes, 217 risk stratification of patients with unstable angina, 218 predicting cardiovascular risk via obesityinduced metabolic complications, 219 and heart failure. 216 Moreover, with the progression of CVDs, injured cells continue to secrete disease-specific EVs 212,220 that reflect cardiac damage, information that can be leveraged as diagnostic biomarkers for CVDs, guide disease-specific therapeutics, and gauge therapeutic responses.…”
Section: Diagnostic and Prognostic Potential Of Evs For Cvd Managementmentioning
confidence: 99%